1997
DOI: 10.1093/rheumatology/36.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone metabolism and cyclosporin A treatment in rheumatoid arthritis

Abstract: A constant dose-dependent side-effect in cyclosporin A (CSA)-treated patients is the appearance of hypertrichosis; this occurs in both sexes and suggests an androgenizing activity. To determine the influence of CSA on peripheral androgen metabolism, we evaluated in rheumatoid arthritis (RA) patients treated with low-dose CSA (3.5 mg/kg/day), during a period of 12 months, plasma levels of testosterone (Tes) and of 5alpha-androstane-3alpha, 17beta-diol glucuronide (Adiol-G), an important peripheral Tes metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
(67 reference statements)
0
17
0
1
Order By: Relevance
“…In women, serum testosterone is 0.78Ϯ 0.27 normal women and 0.20Ϯ0.06 nmol/l in RA patients, respectively. 20) RT-PCR analysis indicated that TNFa induced IL-1a mRNA expression in these primary synovial cells, and DHT significantly inhibited the IL-1a mRNA inducing activity of TNFa (Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…In women, serum testosterone is 0.78Ϯ 0.27 normal women and 0.20Ϯ0.06 nmol/l in RA patients, respectively. 20) RT-PCR analysis indicated that TNFa induced IL-1a mRNA expression in these primary synovial cells, and DHT significantly inhibited the IL-1a mRNA inducing activity of TNFa (Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…• Causes metabolic alterations in liver, muscle and adipose tissue, which may contribute to the development of dyslipidemia and insulin resistance [19] • Acute kidney injury • Hyperlipidemia (especially hypertriglyceridemia) • Hypertension • Gastrointestinal upset and headaches [20] • Hypertrichosis [21] • Increase testosterone level [22] • Gingival overgrowth [23] …”
Section: Side Effects Of Cyclosporin Amentioning
confidence: 99%
“…This suppression of B cell function seems to be indirect effect via decreased IL-6 production by monocytes. Testosterone at physiological concentrations inhibits IL-1 production in synovial macrophages [16], and inhibits G-CSF and M-CSF productions by synovial cells [17], indicating the concept of immnosuppressive and antiinflammatory functions of androgens.…”
Section: Fig (1) Stress-induced Feedback System During Inflammationmentioning
confidence: 99%